Faktor determinan yang mempengaruhi preferensi pengguna terhadap pakaian dan rumah tinggal - Auliya Maula Alqadrie; Laras Primasari; Hanson Endra Kusuma (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Preference is a choice of an object that reflects individual perceptions and attitudes. These perceptions and attitudes tend to be constant so that there is a possibility of similarities in individual clothing and housing preferences. This research is a preliminary study to explore the similarities between fashion and architecture from clothing and residential preferences. This research is qualitative exploratory research with a grounded theory approach—data collection using online questionnaires with a non-random sampling method. The collected text data were analyzed using content analysis (open coding). The results have revealed the similarities between the various factors that are considered in choosing clothes and housing. The study results have also identified eight-factor categories, namely image, comfort, mood, materiality, cleanliness, economy, convenience, and function, and various new keywords that affect individual preferences for clothing and housing